Orthopaedic treatment of metastatic bone disease - Kolarz, Krzysztof; Treder, Mariusz (Contemporary Oncology/Współczesna Onkologia, 2001)
Advances in aggressive methods of treatment of metastatic bone disease result in pain relief and ease of care. Early postoperative mobility permits complex rehabilitation program and positively influences overall health status. The rational approach to treatment of metastatic pathologic fractures includes: 1) selection of the surgical option that allows definite management in one-stage procedure, 2) resection of the pathologic changes addressing all areas of weakened bone, 3) minimising the hospitalisation time in consideration to decreased expected life time, 4) early postoperative recovery of the extremity function, especially among patients with poor tolerance of immobilisation. The selection of surgical management depends on general health status, localisation of the pathologic fracture, extent of bone destruction, histologic origin of the metastasis, and expected duration of the patient survival. In the past the surgical treatment could be considered if the life expectancy was longer than 3 months. Presently even terminative patients should be considered as candidates of surgical treatment because of its analgesic effect and restoration of ambulatory function. Moreover, even the presence of multiple fractures does not preclude surgical management. This review will discuss indications for operative management of metastatic bone disease and advances in surgical techniques along with some treatment solutions depending on the location of the metastasis.